Labour Law Patrimonial Liabilities. General Aspects - COVRIG, Georgiana (Annals of Spiru Haret University. Economic Series, 2014)
The damages under labour law are assessed according to special legal provisions and in the absence of such regulations, civil law regulations must be applied in relation to the prices at the time at which the agreement of will was made or the damaged person may bring the action before the court. In the case of goods’ damage, the damage assessment is done in all cases taking into account the real degree of wear of the asset.